Tanggung Jawab Negara terhadap Penembakan Pesawat MH17 berdasarkan Hukum Internasional - Mangku, Dewa Gede Sudika; Radiasta, I Ketut (Universitas Negeri Semarang, 2019)
The purpose this research were to find out and analyze the form of the State of Ukraina accountability in shooting MH17 Malaysia Air Lines aircraft and knowing and analyzing the accountability of MH17 Malaysia Air Lines airliners to passengers. The type of research used is a type of normative legal research, the approach in this study is the law approach, case approach, and historical approach, the sources of legal material used are primary, secondary and tertiary legal materials. Legal material collection techniques used with document study techniques and legal materials are evaluated, interpreted, argued and discussed descriptively. The results of the study show (1) the responsibility of the Ukraina for Malaysia Air Lines MH17 Aircraft Shooting that the State of Ukraina must be responsible for providing safety and security services for the sovereignty of the air space over its territory by Malaysia Air Lines MH17 in the form of flight navigation services, (2) The Malaysia Airlines airline must be limited to 100,000 SDR for each passenger and Malaysia Airlines. The airline cannot be subject to unlimited liability or exceed 100,000 SDR. Every country is expected to always supervise the airspace which is the sovereignty of the airspace above which becomes the international civil aviation route and to coordinate well with the ICAO (International Civil Aviation Organozation) to maintain the security of international civil aviation.Ã‚Â